PERSPEKTIF PENYEBAB STUNTING DAN KETAHANAN KELUARGA: ANALISIS KUALITATIF TEORI MODAL SOSIAL - Muhammad Fajar Firdausyi; M. Zafar Sidiq; M.Ramadhan Wira N.P.; Agustian Agustian; Irlansyah Arifin; Rizki Saputra (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2025)
Stunting is a chronic nutritional problem that affects the quality of human resources in the future. This study aims to understand the social perspectives on the causes of stunting and its relation to family resilience in Cikembar Subdistrict, Sukabumi Regency. A qualitative approach was employed through in-depth interviews with mothers of stunted children, observations, and document studies. Data were analyzed using Robert Putnam’s social capital theory, which emphasizes the role of social networks, norms, and trust in strengthening family resilience. The findings reveal that social, cultural, and economic factors contribute to stunting, while family resilience is fostered through social support, community solidarity, and family adaptation strategies. This study recommends strengthening social capital at both family and community levels as a sustainable strategy to prevent stunting.